A Net Draft Tube Slurry Airlift Bioreactor for 2,4-D (2,4-Dichlorophenoxyacetic Acid) Pesticide Biodegradation - Znad, Hussein; Ohata, H.; Tade, Moses (The Canadian Society for Chemical Engineering, 2010)
Biodegradation of the pesticides 2,4-D have been investigated in a net draft tube airlift bioreactor at different concentrations (10–160 ppm) and air flow rates (0.75–4 L min−1), employing acclimatised activated sludge. A modification for the glass draft tube airlift bioreactor was proposed in which the draft tube is made of non-woven polypropylene textile net. The experiments were carried out as well in a bubble column (BC) for comparison. The results confirmed that immobilising the activated sludge on the net of the draft tube could enhance the substrates mass transfers and improve the biodegradation rate. A mathematical model was developed to simulate the biodegradation process. The simulated results were in good agreement with the experiments.